2021
DOI: 10.1021/acsptsci.1c00024
|View full text |Cite|
|
Sign up to set email alerts
|

On the Relationship between Classic Psychedelics and Suicidality: A Systematic Review

Abstract: Use of classic psychedelics (e.g., psilocybin, ayahuasca, and lysergic acid diethylamide) is increasing, and psychedelic therapy is receiving growing attention as a novel mental health intervention. Suicidality remains a potential safety concern associated with classic psychedelics and is, concurrently, a mental health concern that psychedelic therapy may show promise in targeting. Accordingly, further understanding of the relationship between classic psychedelics and suicidality is needed. Therefore, we condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 123 publications
(158 reference statements)
1
26
0
1
Order By: Relevance
“…A hallucinogen persisting perception disorder (HPPD) was reported after 10 years of taking LSD with severe psychopathology, war exposer, and previous suicidal behavior. 14 However, a recent systematic review assessing the relationship between psychedelics and suicidality found positive, negative, and mixed findings 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hallucinogen persisting perception disorder (HPPD) was reported after 10 years of taking LSD with severe psychopathology, war exposer, and previous suicidal behavior. 14 However, a recent systematic review assessing the relationship between psychedelics and suicidality found positive, negative, and mixed findings 15 …”
Section: Discussionmentioning
confidence: 99%
“…14 However, a recent systematic review assessing the relationship between psychedelics and suicidality found positive, negative, and mixed findings. 15 Therefore, further evidence is needed to find out the cause and effect association (if any).…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review, Zeifmann et al (2021) examined the relationship between classic psychedelics and suicidality. Results suggest that psychedelic therapy can reduce suicidality in certain clinical psychiatric populations, and that classic psychedelic use may buffer against, and be associated with reductions in suicidality.…”
Section: Psychological and Psychiatric Risksmentioning
confidence: 99%
“…Results suggest that psychedelic therapy can reduce suicidality in certain clinical psychiatric populations, and that classic psychedelic use may buffer against, and be associated with reductions in suicidality. However, in unsafe and unmonitored settings, psychedelic use can, on rare occasions, also lead to fatal consequences, including suicide, but Zeifmann et al (2021) stress the highly limited nature of their source literature, with the majority of the included studies being case studies or small case reports using retrospective data.…”
Section: Psychological and Psychiatric Risksmentioning
confidence: 99%
“…The last two decades have seen a massive resurgence of research into psychedelics largely due to their wide range of therapeutic benefits (e.g., addiction [2][3][4][5] , depression [6][7][8][9][10] , end-of-life distress [11][12][13][14][15] , suicidality [16][17][18] , obsessive-compulsive disorder 19 , migraine 20,21 , phantom-limb pain 22 , for reviews see [23][24][25][26][27][28] ). This has elevated interest in substance-assisted therapies, where conventional therapy is combined with psychedelic sessions.…”
Section: Introductionmentioning
confidence: 99%